RETRACTED: The modern approach to breastfeeding: epidemiology and its importance for moternal and child wellbeing from the public health prospective (A Review of the Lancet Breastfeeding Series) - L. V. Abolyan; S. V. Novikova (Сеченовский вестник, 2017)
RETRACTED ARTICLEBreastfeeding remains relevant in the 21st century. The current research into its unique properties attracted increased attention to breastmilk. This paper reviews the Lancet article “Breastfeeding in the 21st century: epidemiology, mechanisms, and lifelong effect” (Lancet, 2016). The review dwells upon breastfeeding international epidemiology; breastfeeding effect on maternal and child outcomes from the evidence based medicine prospective; the possible decrease in the number of preventable maternal and child deaths if breastfeeding practice is scaled up to conditionally optimal level.